„The Shard” – one possible model of discrimination of women - Kispál-Vitai, Zsuzsanna; Németh, Julianna (PTE KTK Műhelytanulmányok, 2021)
It is almost a cliché in social sciences today to do gender research. Researchers did exhaustive investigations about the gender wage gap, career, and developmental prospects. The available data about women’s progress (or rather the lack of it) at the workplace is overwhelming, but these are mostly descriptive. Though these presented a comprehensive picture of the phenomenon, they did not provide the reasons for discrimination, only clarified the symptoms. Our article aims to create a new framework utilizing existing data. We suggest a new model that has explanatory value and attempt to present the reasons for the treatment of women. Our theoretical model focuses on decision-making. Our conclusion is – based on prototype heuristics and bounded rationality – that four factors influence decision-making about women in the workplace: cognitive development of the individual, societal expectations, power demands, and accessible data in the environment. Exploring these can contribute to the improvement of women progressing to higher-level jobs by uncovering the reasons for discrimination.